Mesoscale phase-field modeling of silver dissolution in Cast Stone with AgM granules - Hu, Shenyang; Li, Yulan; Asmussen, R. Matthew (Frontiers in Nuclear Engineering, 2025)
A mesoscale model is developed to study silver (Ag) dissolution in Cast Stone (CS) matrix containing silver mordenite (AgM) particles. The model captures microstructure-dependent thermodynamic and kinetic properties, including multispecies diffusion, redox reactions, and Ag precipitation. Simulations show that Ag-rich precipitate formation at the AgM/CS interface slows dissolution by reducing chemical potential gradients and diffusivity, while oxidation reactions enhance Ag release by increasing retention around unreacted reagents (e.g., slag, cement). Smaller AgM particles dissolve more rapidly due to shorter diffusion paths. This model offers a mechanistic framework to assess how microstructure and redox chemistry influence Ag retention and can be integrated with geochemical speciation models for multiscale performance evaluation of nuclear waste forms.